The impact of fertiliser subsidy and new variety of paddy on Malaysian paddy/rice industry - Shamsudin, Mad Nasir; Ramli, Nurul Nadia; Radam, Alias; Mohamed, Zainal Abidin (Universiti Putra Malaysia Press, 2015)
Rice is a staple food for the Malaysian population. Special attention is always given by the government to ensure the sustainability of the Malaysian paddy/rice industry. In order to encourage paddy farmers to increase paddy production, a food security policy for the paddy/ rice sector has been implemented by the government towards self-sufficiency by 2020. There are three types of government intervention on Malaysian paddy and rice industry namely fertiliser subsidy, price support and import restriction or quota. There would be some impact to the industry if the government decides to implement a trade liberalisation policy. This is because trade liberalisation involves removing barriers to trade between different countries. Therefore, it would cause the supporting elements of the industry to be limited. In view of this this study has made its main objective the simulation of the impact of a fertiliser subsidy on the Malaysian paddy and rice industry. The methodology used is the system dynamics model. In addition, this study also attempts to simulate the impact of improvement in yield on the performance of the system. The simulation results suggest that there would be a positive impact to the industry with the implementation of the current policy for fertiliser subsidy. Yield obtained would increase with the implementation of the fertiliser subsidy. Consequently, it would increase paddy production. Paddy production would decrease if the government decides to remove the fertiliser subsidy. Hence the self sufficiency level (SSL) also would decrease. Due to the reduction in production, the importation of rice seems unavoidable in order to meet the demand. Meanwhile, due to population growth, the government needs to find alternative policies to sustain the industry and increase imports in order to ensure adequate supply of rice for the Malaysian population. The simulation results indicate that the introduction of a new variety of paddy leads to increase in yield, and in turn to increase in the production level. The percentage increase in yield and production is about 3% per year.